Semilinear Dirichlet problem for the fractional Laplacian. (April 2020) - Bogdan, Krzysztof; Jarohs, Sven; Kania, Edyta
Abstract: We give a general framework and results on existence, representation, and uniqueness of solutions to the semilinear problem for the fractional Laplacian with Dirichlet conditions on the complement and at the boundary of general open sets.